Propuesta de un modelo de gestión por procesos para el área administrativa de la empresa NEXTEIDCAP CIA. LTDA. año 2014 - Cruz Pérez, Karolinne Vanessa (2014)
This thesis has been developed in-NEXTEICAP Cia. Ltda., Which is relatively new in the training market. The main problem with this company is that it has a process management model, as the efficiency and effectiveness of each of the activities with internal and external customers has affected their finances. To solve this problem, we applied the knowledge learned during the academic processes at the Masters. Once detected the problem, the analysis of basic management concepts and quality management, which helped to improve the creation of new processes that contribute to the optimization of the operation proceeded. Through research, a diagnosis of the current situation was obtained, relevant aspects such as lifting existing processes, value chain, indicators, process flow, strengths-weaknesses and improvements that can be implemented analyzed